Treatment trends for retinopathy of prematurity in the UK: active surveillance study of infants at risk. Issue 3 (21st March 2017) - Adams, Gillian G W; Bunce, Catey; Xing, Wen; Butler, Lucilla; Long, Vernon; Reddy, Aravind; Dahlmann-Noor, Annegret H
Abstract : Objectives: To estimate the incidence of severe retinopathy of prematurity (ROP) requiring treatment and describe current treatment patterns in the UK. Design: Nationwide population-based case ascertainment study via the British Ophthalmic Surveillance Unit and a national collaborative ROP special interest group. Practitioners completed a standardised case report form (CRF). Setting: All paediatric ophthalmologists providing screening and/or treatment for retinopathy in the UK were invited to take part. Participants: Any baby with ROP treated or referred for treatment between 1 December 2013 and 30 November 2014, treated with laser, cryotherapy, vascular endothelial growth factor (VEGF) inhibitor or vitrectomy/scleral buckling, or a combination. Main outcome measure: Incidence of ROP requiring treatment. Results: We received 370 CRFs; 327 were included. Denominator from epidemiological data: 8112 infants with birth weight of <1500 g. The incidence of ROP requiring treatment was 4% (327/8112, 95% CI 3.6% to 4.5%). Median gestational age was 25 weeks (IQR 24.3–26.1), and median birth weight 706 g (IQR 620–821). Median age at first treatment was 80 days (IQR 71–96). 204 right eyes (62.39%) had type 1 ROP, and 27 (8.26%) had aggressive posterior ROP. Infants were also treated for milder disease: 9 (2.75%) right eyes were treated for type 2 ROP, and 74 (22.63%) for disease milder than type 1 with plus or preplus, which we defined here as 'type 2 plus' disease. First-line treatment was diode laser photoablation of the avascular retina in 90.5% and injection of VEGF inhibitor in 8%. Conclusions: ROP treatment incidence in the UK is 2.5 times higher than previously estimated. 8% of treated infants receive intravitreal VEGF inhibitor, currently unlicensed. Research is needed urgently to establish safety and efficacy of this approach. Earlier treatment and increasing numbers of surviving premature infants require an increase in appropriate eye care facilities and staff. Trial registration number: NCT02484989.